Note taking on listening in academic context: EFL students’ perception - Imelda Darmayanti Manurung (Institute of Computer Science (IOCS), 2023)
Learning listening in academic context course aims to hone students' listening skills in recognizing main ideas and important information contained in academic texts. For this reason, students must be observant in listening while digging for the details. It needs the skill to help to recall and gain the knowledge: note-taking, a technique of to record a key information. Therefore, this study aims to describe the English as a Foreign Language (EFL) students’ perception of applying two of note taking technique: linear note and mind mapping styles while doing listening tasks. A questionnaire were administered to probe the perceptions about the listening learning situation and attitude to the use of note taking on listening in academic context subject. Based on the data analyzed, note taking is very helpful and useful for the students to record the information.